Aldosterone Response in Severe Hypokalemia and Volume Depletion: A Case Report and Review of the Recent Research - Keiko Kai; Naoto Tominaga; Daisuke Uchida; Nanae Fukai; Yumie Matsuura; Susumu Uda; Akio Yokochi (Case Reports in Nephrology)
We report a case of severe hypokalemia and volume depletion complicated by chronic watery diarrhea resulting from chronic alcoholism in a 57-year-old man. Prompt replacement of normal saline with potassium chloride and cessation of alcohol intake resulted in a favorable outcome. We discuss the pathophysiology of the case, emphasizing the response of aldosterone in both hypokalemia and volume depletion, and provide a review of recent research.